Project Monitoring and Scheduling of Water Supply Project Using Primavera P6 A Review - Ravi Patel; Dharmendra Prajapati (International Journal of Scientific Research in Civil Engineering, 2022)
Water is of fundamental importance for human life and plays an important role in many biological and chemical systems. Only 0.3% of the water resources in the world are usable. Scarcity of water has become widespread all over the world. Current methods for water scarcity assessment are mainly based on water quantity and seldom consider water quality. Population growth and urban development aspect dramatically alter natural watershed ecosystem structure and functions and stress water resources. The demand of time is review water quantity and water quality issues, as well as water supply challenges in an urban environment. So that more than a billion people in the developing world lack safe drinking water. About three billion people live without access to adequate sanitation systems necessary for reducing exposure to water-related diseases. Water is a valuable fundamental asset for life. Availability of sufficient water resource in any region effects socio economic development as well as better quality of life. Lack of water resource is determinant the poor quality of life. In this study proposing review of literatures related to water supply system.